Identification of genes involved in energy metabolism in preeclampsia and discovery of early biomarkers - Li, Ruohua; Zhou, Cuixia; Ye, Kejun; Chen, Haihui; Peng, Mengjia (Frontiers in Immunology, 2025)
BackgroundPreeclampsia is a complex pregnancy condition marked by hypertension and organ dysfunction, posing significant risks to maternal and fetal health. This study investigates the role of energy metabolism-associated genes in preeclampsia development and identifies potential early diagnostic biomarkers.MethodsPreeclampsia datasets from Gene Expression Omnibus were analyzed for batch correction, normalization, and differential expression. Enrichment analyses using gene ontology, Kyoto Encyclopedia of Genes and Genomes, and gene set enrichment were performed. Protein-protein interaction networks were constructed to identify key genes, and regulatory networks involving transcription factors, miRNAs, and RNA-binding proteins were established. Differential expression was validated with receiver operating characteristic curve analyses, and immune infiltration was assessed.ResultsSix energy metabolism-related genes were identified. Enrichment analyses revealed their involvement in glycolysis, gluconeogenesis, lipid transport, bone remodeling, and glucagon secretion. Key differentially expressed genes included CRH(Corticotropin-Releasing Hormone), LEP(Leptin), PDK4(Pyruvate Dehydrogenase Kinase Isozyme 4), SPP1(Secreted Phosphoprotein 1), and SST(Somatostatin). PDK4 exhibited moderate accuracy in receiver operating characteristic analysis. Immune infiltration analysis indicated significant differences between preeclampsia and control samples. qRT-PCR confirmed LEP and CRH increased, while SPP1 expression in preeclampsia samples.ConclusionDysregulated energy metabolism-related genes may contribute to preeclampsia through metabolic and immune changes. Identifying these genes aids in understanding preeclampsia’s molecular basis and early diagnosis. Future studies should validate these markers in larger cohorts and explore targeted treatments.